Foundations of a planned economy, 1926-1929 - Carr, Edward Hallett; Davies, R.W. (London : Macmillan, 1978)
This volume examines Soviet foreign relations from 1926 to 1929. Part 1 covers Soviet diplomatic relations with the major capitalist countries, and the procedures of the Communist International.
Vol. 3, Part 3.
Includes bibliographical references and index.
lje 23/01/2019
Loans
Keywords: Economy-Soviet Union; Social conditions; Russia